An unusual bronchial obstruction in a fit young man. (9th January 2013) - Freeman, Anna; Weeden, David; Wilkinson, Jane; Kurukulaaratchy, Ramesh J
Abstract : We describe the case of a previously well young man who presented acutely to hospital with a history of progressive chest symptoms and systemic upset. At admission, clinical evidence of left upper lobe collapse on respiratory examination and chest x-ray gave rise to significant clinical concern. Initial assessment by CT suggested a possible aspirated foreign body in the left upper lobe bronchus with distal left upper lobe collapse. Subsequent rigid bronchoscopy identified a solid abnormality totally occluding the left upper lobe bronchus, which did not appear to be a foreign body. The patient became progressively more unwell with clinical signs of chest sepsis and failed to settle with medical therapy. A decision was made to undertake a lobectomy to remove the collapsed lobe and obstructing endobronchial lesion. Histology confirmed that the cause of bronchial obstruction was a mesenchymoma (pulmonary hamartoma).